A Novel Reprocessable and Recyclable Acrylonitrile–Butadiene Rubber Based on Dynamic Oxime‐Carbamate Bond. Issue 17 (28th February 2019) - Wang, Wenyan; Song, Qingfei; Liu, Qing; Zheng, Hua; Li, Chunmei; Yan, Yi; Zhang, Qiuyu
Abstract: The covalent cross‐linked rubber has outstanding mechanical properties and chemical resistance, making it possible for a wide range of applications. Towards efforts to resource waste and environmental pollution, rubber recycling is a concerning problem. However, it is a big challenge to endow the most widely used commercial rubber systems with recyclability. In this paper, a novel reprocessable and recyclable acrylonitrile–butadiene rubber (NBR) is developed by introducing oxime‐carbamate bonds into the raw NBR. Amidoxime NBR is prepared by a nucleophilic addition reaction of hydroxylamine hydrochloride and raw NBR, and then cross‐linked amidoxime NBR using different amounts of toluene diisocynate (TDI). Results show that the obtained material exhibits good reprocessable property; the repairing efficiency exceeds 90% after two remoldings. In addition, it also has better mechanical properties: A tensile strength reaching a maximum value of 4.85 MPa when TDI cross‐linker is 15.36 wt%, which is superior to vulcanized NBR (3.18 MPa). Abstract : Recently, rubber recycling has been a concerning problem. In this paper, a novel reprocessable acrylonitrile–butadiene rubber (NBR) is developed by introducing dynamic oxime‐carbamate bonds into raw NBR. Owing to the simple preparation process and largely available NBR, this work has the potential to offer an efficient route towards practical applications.